Life Cycle Testing of Hermetic Compressors With Alternatives to CFC-12 - Sukumar Devotta; Nitin N Sawant; Shailesh N Joshi (Mesin, 1999)
Life cycle tests of hermetic compressors were conducted using a specially designed test rig that employs a gas cycle. They were conducted at an ambient temperature of 50"C and suction and discharge pressures of 2.2 bar and 18.5 bar respectively. The oil temperature was maintained between 80- I 00"C. The duration of test was 2000h.After completion of the test, the oil samples were tested for total acid number and metal contents (Cu, Fe and Al). Any chemical degradation of refrigerant sample was assessed using NMR and F T-IR spectroscopes. The wear effects of compressor parts were measured using perthography.An assessment of conventional mineral oil with CF C-12 and various grades of hydrocarbon (HC-290 and HC-600a) blends including DIN grade, CARE-30, a blend of HC-290/HC-600a from Indian sources, destenched LPG, and commercial grade LPG has been done. HFC-134a and Polyol ester oil (POE) combination has also been studied. The comprehensive test results from the above assessment and comparative ratings are presented